Medicine of the Future Risk Assessment, Elimination or Mitigation, and Action Plans for 28 Diseases and Medical Conditions - Meunier, Yann (Springer International Publishing : Imprint: Springer, 2014)
This book outlines risk assessments for 28 diseases and medical conditions including the following aspects: genetics, biochemistry, serology, past medical history, family history, co-morbidities, age, gender, ethnicity, nutrition and lifestyle. Recommendations are made for how to avoid, eliminate or mitigate risks. Preventing measures concerning chemical compound intake, lifestyle and nutrition are proposed. The unique content and approach of the book to chronic disease management make it a state-of-the-art reference work, addressing a missing component of medical care and reflecting the cutting edge of preventive medicine.